Development of Learning Media Using SAC Software in Coordinate Systems Concepts for 11th Grade Senior High School Students - Budiono, Annisa Viantami (Universitas Sultan Ageng Tirtayasa, 2023)
The rapid development of technology has a positive impact on the world of education, one of which is in the development of learning media. The aim of this research is to determine the feasibility and response of teachers and students to audio-visual learning media coordination on the Coordinate System concept by showing the expert's validation. The research was carried out using the modified Research and Development method which includes definition, design, and development. Learning concepts are limited only to the Coordinate System. The first step is observation. Observations were conducted on 168 eleventh grade students from four different schools in the Blitar city, Indonesia. The results show that the concept which they find difficult to understand is the Coordinate System. On the other hand, the learning method that makes students master the concept more quickly is the listening and seeing style learning method. The problem is formulated into two, namely how the feasibility of coordinating audio-visual learning media and how the response of teachers and students to the learning media. The results of the research are Audio Visual Coordination learning media in the form of an Android-based application that contains animated and explanatory videos. The results of validation by three experts consists of media, concept and language experts were 90.45%, 88% and 88.6% with very good categories. While the results of the teacher's response were 92% in the very good category and 82% for students in the good category.